Prostatic Hyperplasia (BPH) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article presents information from local and foreign sources about the disease of prostate gland hyperplasia (BPH): causative factors, symptoms, types, complications, treatment and prevention. In the diagnosis of compensated, subcompensated, decompensated and terminal stages of prostatic hyperplasia, information is provided about the patient's questionnaire, urological examination and a number of other laboratory and instrumental examination methods.